Formulation and evaluation of taste mask pellets of granisetron hydrochloride as oro dispersible tablet - Nilesh Choudhary; Jasmine Avari (Universidade de São Paulo, 2015)
Orally disintegrating systems have carved a niche amongst the oral drug delivery systems due to the highest compliance of the patients, especially the geriatrics and pediatrics. In addition, patients suffering from dysphagia, motion sickness, repeated emesis and mental disorders prefer these medications because they cannot swallow large quantity of water. Further, drugs exhibiting satisfactory absorption from the oral mucosa or intended for immediate pharmacological action can be advantageously formulated in these dosage forms. However, the requirements of formulating these dosage forms with mechanical strength sufficient to withstand the rigors of handling and capable of disintegrating within a few seconds on contact with saliva are inextricable. The purpose of this research was to mask the bitter taste of granisetron hydrochloride. To mask the taste Kollicoat(r) Smartseal 30D was used as coating polymer for pellet coating. The coated pellets of the drug was directly compressed with different superdisintegrant as AC-Di-Sol, Explotab and Kollidon CL in different concentration 5.0-7.5% w/w into an ODT. The prepared tablets were evaluated for hardness, friability, weight variation, wetting time, wet absorption ratio, in-vitro disintegration time and in vitro dissolution studies. Tablets exhibited quick disintegration characteristics with Kollidon CL in concentration 7.5% w/w i.e., within 20 seconds, which is characteristic of orally disintegrating dosage forms. More than 98% of drug was released from the formulations within 15 minutes. Formulations subjected to stability testing as per the ICH guidelines for 3 months, indicated stability with no change in taste, hardness, drug content, disintegration time and dissolution profiles. Thus, the results conclusively demonstrated successful masking of taste and rapid disintegration of the formulated dosage forms in the oral cavity.